PsycEXTRA Dataset 2009
DOI: 10.1037/e733962011-001
|View full text |Cite
|
Sign up to set email alerts
|

Flight Attendant Fatigue, Part I: National Duty, Rest, and Fatigue Survey

Abstract: This document is disseminated under the sponsorship of the U.S. Department of Transportation in the interest of information exchange. The United States Government assumes no liability for the contents thereof.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
41
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 7 publications
6
41
0
1
Order By: Relevance
“…On average, US flight attendants wait 16 min for transportation, with 49 min spent overall on travel to the rest facility, leaving less than eight hours for check-in, meals, personal hygiene, and sleep when given a minimum rest period of nine hours (Avers et al, 2009). Only 21% of the regulations and 7% of the CBAs had a protective provision requiring operators to give crewmembers prone rest.…”
Section: Sleep and Rest Requirementsmentioning
confidence: 97%
See 1 more Smart Citation
“…On average, US flight attendants wait 16 min for transportation, with 49 min spent overall on travel to the rest facility, leaving less than eight hours for check-in, meals, personal hygiene, and sleep when given a minimum rest period of nine hours (Avers et al, 2009). Only 21% of the regulations and 7% of the CBAs had a protective provision requiring operators to give crewmembers prone rest.…”
Section: Sleep and Rest Requirementsmentioning
confidence: 97%
“…A "prone rest" rule separates actual sleep time from other activities during the rest period and allows flight attendants "behind-the-door" or "prone" rest protection. One change to US rules that has been suggested is to start the scheduled rest period after arrival at the rest facility (Avers et al, 2009). …”
Section: Sleep and Rest Requirementsmentioning
confidence: 99%
“…The aviation industry offers 24/7 service, which creates a number of challenges for cabin crew. They often experience irregular schedules, long duty periods, circadian rhythm disruption, sleep loss and high workload, which have all been shown to be contributing factors to cabin crew fatigue [1][2][3][4][5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore not surprising that cabin crew experience work-related fatigue. In a large-scale survey with 9,180 cabin crew, 84% reported being fatigued while on duty, of which 71% reported that their safety-related performance was affected, and 52% reported that they had 'nodded off' while working on a flight 1) .…”
Section: Introductionmentioning
confidence: 99%
“…Among the factors investigated are circadian dysrhythmia, recycled air, fatigue, shifting work schedules, radiation exposure, and the lifting and handling of heavy objects (Ballard, Lagorio, De Angelis, & Verdecchia, 2000; Dresel & Boutros, 2001; Griffiths & Powell, 2012; Lauria, Ballard, Caldora, Mazzani, & Verdecchia, 2006; Schaub et al, 2007; Sharam, 2007; Suvanto, Partinen, Harma, & Ilmarinen, 1990). Other research has examined how aspects of the job—extended time away from home, irregular work schedules, long hours, and difficult passengers— contribute to work-related stress, psychological well-being, and job dissatisfaction (Avers, King, Nesthus, Thomas, & Banks, 2009; Avers et al, 2011; Gunnarsdottir, Sveinsdottir, Bernburg, Fridriksdottir, & Tomasson, 2006; Liang & Hsieh, 2005; Salinger, Jesilow, Pontell, & Geis, 1985). A few studies address organizational factors—the lack of a clear career path, limited job resources, and lack of immediate supervision—that contribute to stress and turnover (Chen & Chen, 2012; Liang & Hsieh, 2005).…”
mentioning
confidence: 99%